The role of transvaginal ultrasonography in evaluating the endometrium of women with postmenopausal bleeding - Ibrahim, Amal M.; Elioba, John L. R.; Ali, Fahma A.; M. Mohamed, Muna; M. Omar, Ahkam; J.Osman, Anab; D. Warsame, Fardowso; Abdi Ali, Ramla; Emmanuel, Okurut; Hakizimana, Theoneste (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Postmenopausal bleeding (PMB) is a clinically relevant symptom that should be evaluated promptly due to its linkage to endometrial pathology, including endometrial cancer. For women who present with PMB, transvaginal ultrasonography (TVUS) has become a first-line, non-invasive imaging method for assessing the endometrium. The objective of this review article is to compile the most recent data regarding the diagnostic utility, uses, limitations, and technological advancement of transvaginal ultrasonography in evaluating endometrial pathology in postmenopausal women. Recent clinical research, case reports, and multicentre trials were thoroughly examined with an emphasis on the use of TVUS in the diagnosis of endometrial atrophy, hyperplasia, polyps, fibroids, and cancer. Further assessment was conducted on its usefulness in specific groups, including women on hormone replacement therapy (HRT) and those experiencing recurrent PMB. With a cut-off value of less than 4 mm, TVUS has a good negative predictive value for endometrial cancer and is useful for evaluating endometrial thickness. It greatly lessens the need for invasive procedures in low-risk patients, but it cannot replace a histopathology. Diagnostic accuracy has increased due to recent advancement including 3D imaging, Doppler flow analysis, and artificial intelligence integration. Its usefulness in directing therapeutic management and enhancing early diagnosis is supported by case studies and clinical trials. For the first assessment of postmenopausal bleeding, transvaginal ultrasonography is an essential, safe, and cost-effective procedure. Its increased usage in gynaecologic diagnostics is supported by its high sensitivity and recent technological advancements, but histological confirmation is still necessary in cases where questionable results are found.